Pengaruh Antioksidan Alami pada Berat Testis Mencit (Mus musculus) yang Terpapar Senyawa Kimia Plastik - Atang Atang; Endah Sri Palupi (Pascasarjana Universitas Jenderal Soedirman, 2020)
Plastic is a material that is often found in everyday life, both for household needs, offices, agriculture/plantations, industry, etc. One type of plastic that is commonly used is polycarbonate plastic (polycarbonate / PC). The main ingredient in polycarbonate plastics is a compound 2,2-bis (4-hydroxyphenyl) propane known as bisphenol A (BPA). The purpose of this study was to determine the effect of natural antioxidants on the testicular weight of adult male mice exposed to the chemical compounds that make up the plastic. This study used a completely randomized design (CRD) with six treatments and five replications. The treatments included two control groups and four other groups treated with plastic boiled water and natural antioxidants. Plastic boiled water and antioxidants were given orally to 0.25 ml of male mice every day during the study. Quantitative data were analyzed using ANOVA and BNT. Based on the results of the research that has been carried out, it can be concluded that the provision of natural antioxidants for 21 days in mice (Mus musculus) exposed to plastic chemical compounds has an effect on decreasing the testicular weight of male mice in K (-) treatment / negative control. Based on data analysis through statistical tests that have been carried out, the series of natural antioxidant treatments for mice exposed to plastic chemical compounds for 21 days did not significantly affect the testicular weight of mice.